2021
DOI: 10.1002/oa.3048
|View full text |Cite
|
Sign up to set email alerts
|

Fish vertebrae as archeological biomarkers of past marine ecological conditions: Comparison of mercury levels in Chilean swordfish between the Middle Holocene and the modern period

Abstract: The ocean has always been a source of inspiration for past and present civilizations, especially for those involved in fishing activities. The regular fishing of large pelagic fish by past societies using harpoons has been demonstrated, with several studies reporting the discovery of an important fishery of large pelagic fish (including swordfish) dating from as early as the sixth millennium BCE on the North Chilean Pacific Coast. The swordfish (Xiphias gladius) is a cosmopolitan, highly migratory species foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
1
1
0
1
Order By: Relevance
“…Similar to findings in the ENP (Carey & Robison 1981, Dewar et al 2011, the swordfish tagged off the coast of northern Chile revealed daytime depths that were much shallower than those documented for offshore waters (Abascal et al 2010). The daily depth records also showed considerable basking activity, a behavior that has supported the use of harpoon methods in this region since the sixth millennium BCE (Béarez et al 2016, Biton-Porsmoguer et al 2022. The relatively shallow daytime existence aligns with areas of low DO levels.…”
Section: Discussionsupporting
confidence: 74%
“…Similar to findings in the ENP (Carey & Robison 1981, Dewar et al 2011, the swordfish tagged off the coast of northern Chile revealed daytime depths that were much shallower than those documented for offshore waters (Abascal et al 2010). The daily depth records also showed considerable basking activity, a behavior that has supported the use of harpoon methods in this region since the sixth millennium BCE (Béarez et al 2016, Biton-Porsmoguer et al 2022. The relatively shallow daytime existence aligns with areas of low DO levels.…”
Section: Discussionsupporting
confidence: 74%
“…Lamentablemente, el estado de esta investigación nos limita en establecer efectivamente si la ingesta y/o inhalación de arsénico son los causantes de estas patologías, o si todos los miembros de las comunidades participaron activamente en el sistema de parentesco propuesto. Por otro lado, tampoco podemos descartar que la ingesta de otros metales pueda estar causando las enfermedades aquí mencionadas, como se ha sugerido en recientes trabajos, los cuales han detectado la presencia elevada de cadmio y cobre en restos humanos (Huerta, 2019), y de mercurio en recursos marinos consumidos en tiempos prehistóricos (Biton-Porsmoguer et al, 2022). Todos estos metales tienen el potencial de generar enfermedades congénitas (Winter, 1982;da Rocha et al, 2011;Taboada et al, 2017;Bjorklund et al, 2019).…”
Section: Conclusionesunclassified
“…Atmospheric inputs represent the main source of mercury in the Mediterranean Sea, representing annual fluxes of about 37.7 Mg y -1 THg and 0.4 Mg y -1 MeHg, with higher THg and MeHg concentrations being recorded in the Western basin compared to the Eastern basin, both in seawater and sediments (Cossa et al, in press). The origin of Hg in the oceans is natural, ancient and anthropogenic (Biton-Porsmoguer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%